2018
DOI: 10.1186/s13662-018-1662-3
|View full text |Cite
|
Sign up to set email alerts
|

Permanence, partial survival, extinction, and global attractivity of a nonautonomous harvesting Lotka–Volterra commensalism model incorporating partial closure for the populations

Abstract: We propose and study a nonautonomous harvesting Lotka-Volterra commensalism model incorporating partial closure for the populations. By using the differential inequality theory we obtain sufficient conditions that ensure the extinction, partial survival, and permanence of the system. By applying the fluctuation lemma we establish sufficient conditions that ensure the extinction of one of the components and the stability of the the other one. For the permanent case, by constructing a suitable Lyapunov function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…During the last decade, many scholars ( [2][3][4][5][6][7][8][9][10][11][12][13][14][16][17][18][19][20][21][22][23][24][25]) investigated the dynamic behaviors of the mutualism and commensalism model. Some substantial progress has been made on the stability, permanence and extinction of the mutualism model.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, many scholars ( [2][3][4][5][6][7][8][9][10][11][12][13][14][16][17][18][19][20][21][22][23][24][25]) investigated the dynamic behaviors of the mutualism and commensalism model. Some substantial progress has been made on the stability, permanence and extinction of the mutualism model.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many scholars investigated the dynamic behaviors of the stagestructured species, see [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], and the references cited therein. In constructing a stagestructured model, two different ideas were applied.…”
Section: Introductionmentioning
confidence: 99%
“…(1.8) They showed that system (1.8) admits a unique positive equilibrium which is globally asymptotically stable. Many scholars [26][27][28][29][30][31][32][33][34][35][36][37][38][39] used the idea of Aiello and Freedman to establish stage-structured ecological models. For example, Chen et al [28] studied the persistence property of the following stage-structured predator-prey model:…”
Section: Introductionmentioning
confidence: 99%
“…An example of it is that remora are specially adapted to attach themselves to larger fish that provide locomotion and food. In the last decades, commensalism has attracted the attention of many researchers ( [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]). Complicated dynamics have been found in the study.…”
Section: Introductionmentioning
confidence: 99%
“…For more details, see [6][7][8]. Combining this with (1), we propose the following commensalism model:…”
Section: Introductionmentioning
confidence: 99%